The Indigenous South American Tsimane Exhibit Relatively Modest Decrease in Brain Volume With Age Despite High Systemic Inflammation. (26th May 2021) - Irimia, Andrei; Chaudhari, Nikhil N; Robles, David J; Rostowsky, Kenneth A; Maher, Alexander S; Chowdhury, Nahian F; Calvillo, Maria; Ngo, Van; Gatz, Margaret; Mack, Wendy J; Law, E Meng; Sutherland, M Linda; et al.
Abstract: Brain atrophy is correlated with risk of cognitive impairment, functional decline, and dementia. Despite a high infectious disease burden, Tsimane forager-horticulturists of Bolivia have the lowest prevalence of coronary atherosclerosis of any studied population and present few cardiovascular disease (CVD) risk factors despite a high burden of infections and therefore inflammation. This study (a) examines the statistical association between brain volume ( BV ) and age for Tsimane and (b) compares this association to that of 3 industrialized populations in the United States and Europe. This cohort-based panel study enrolled 746 participants aged 40–94 (396 males), from whom computed tomography (CT) head scans were acquired. BV and intracranial volume ( ICV ) were calculated from automatic head CT segmentations. The linear regression coefficient estimate β ^ T of the Tsimane ( T ), describing the relationship between age (predictor) and BV (response, as a percentage of ICV ), was calculated for the pooled sample (including both sexes) and for each sex. β ^ T was compared to the corresponding regression coefficient estimate β ^ R of samples from the industrialized reference ( R ) countries. For all comparisons, the null hypothesis β  T = β  R was rejected both for the combined samples of males and females, as well as separately for each sex. Our results indicate that the Tsimane exhibit a significantly slower decrease in BV with age than populations in the United States and Europe. Such reduced rates of BV decrease, together with a subsistence lifestyle and low CVD risk, may protect brain health despite considerable chronic inflammation related to infectious burden.